MARKERS OF INFLAMMATION AND ANTIOXIDANT PROTECTION IN THE ORAL FLUID OF CHILDREN WITH DIFFERENT BODY MASS INDEX BEFORE AND AFTER THE USE OF A MUCOSE‒ADHESIVE GEL BASED ON LIPOPOLYSACCHARIDE - Reyzvikh, O.E.; Shnaіder, S.A.; Ivanov, V.S.; Babenya, A.A.; Klenovskaya, S.V. (World of Medicine and Biology, 2021)
In medical practice, bacterial endotoxins are used primarily to stimulate immunity and nonspecific resistance of the organism. Lipopolysaccharide has a pro-inflammatory effect, stimulating the production of pro ‒ inflammatory cytokines by leukocytes (TNF ‒ α, IL ‒ 1, IL ‒ 6, etc.). However, in small doses, endotoxin stimulates the body's defense systems, transferring them from a state of rest to the stage of active action. Such properties of small doses of lipopolysaccharide served as the basis for its clinical use. Oral applications of the proposed lipopolysaccharide-based gel normalize oral microbiocenosis (decrease of urease activity and degree of dysbiosis), and significantly increase the level of inflammation markers in all groups of children by body mass index, contributing to the transition of inflammatory processes to the active phase; significantly reduce the level of pathological processes in the parodontium of children due to the activation of physiological inflammation.
Keywords: children; inflammation; body mass index; oral fluid; lipopolysaccharide; dental diseases